HUBUNGAN AKTIVITAS FISIK DENGAN TINGKAT KEBUGARAN JASMANISISWA EKTRAKURIKULER FUTSAL MAN 2 BUKITTINGGI - Puji Rahmat; Khairuddin; Haripah Lawanis; Mardepi Saputra (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study is motivated by the importance of physical activity in supporting the physical fitness of students, specifically those participating in the futsal extracurricular program. The study aims to determine the relationship between physical activity and the physical fitness levels of futsal extracurricular students at MAN 2 Bukittinggi. It employs a correlational research design with a total sample of 25 students selected using the total sampling technique. Physical activity was measured using the PAQ-A, while physical fitness was assessed using the Indonesian Student Fitness Test (TKSI). Data analysis involved normality tests, linearity tests, and the Pearson Product Moment correlation test at a significance level of α = 0.05. The results indicate that the data for both physical activity and physical fitness were normally distributed (sig. 0.059 and 0.095) and exhibited a linear relationship (Deviation from Linearity = 0.218). The correlation test yielded an r-value of 0.780 (p < 0.001), demonstrating a positive, strong, and significant relationship between physical activity and the physical fitness of the futsal extracurricular students at MAN 2 Bukittinggi. Physical activity contributed 60.8% to physical fitness, while the remaining 39.2% was influenced by other factors not examined in this study.